EFEKTIVITAS BIMBINGAN KELOMPOK MINDFULNESS JOURNALING UNTUK MENINGKATKAN REGULASI EMOSI SISWA SEKOLAH MENENGAH ATAS (Studi Quasi Eksperimen Pada Siswa Kelas X SMA Negeri 1 Ciruas) - Inggrit Putri Samudra; Raudah Zaimah Dalimunthe; Meilla Dwi Nurmala (STKIP Subang, 2026)
Emotion regulation is an important developmental task for senior high school students, yet a preliminary study at SMAN 1 Ciruas showed that 68.1% of 426 students (from the Student Needs Questionnaire) had not been able to manage their emotions adaptively, and about 112 students had spontaneously used unstructured writing to release negative emotions. This study aimed to describe the level of students' emotion regulation and to examine the effectiveness of group guidance using mindfulness journaling in improving it. A quasi-experimental method with a non-equivalent control-group design was used, involving 20 tenth-grade students selected through purposive sampling: 10 in the experimental group, who received six sessions of mindfulness-journaling-based group guidance, and 10 in the control group, who received conventional group discussion. Data were collected using the adapted Emotion Regulation Questionnaire-Process Model (ERQ-30) developed by Preece and Gross. Because the Shapiro-Wilk normality test showed the data were not normally distributed, hypothesis testing used the non-parametric Mann-Whitney U Test. Results showed a significant difference between groups for both adaptive strategies (p < 0.001) and maladaptive strategies (p = 0.003). The experimental group's adaptive score rose from 68.7 to 91.6 (N-Gain 0.64) and its maladaptive score fell from 85.5 to 61.1 (N-Gain -1.4), both markedly larger changes than in the control group. These findings indicate that mindfulness-journaling-based group guidance is effective in increasing adaptive emotion-regulation strategies and reducing maladaptive ones among senior high school students.